Effects of copper on the photosynthesis of intact chloroplasts: interaction with manganese - Pádua, Mário (2016)
Highly purified, intact chloroplasts were prepared from pea (Pisum sativum L.) and spinach (Spinacia oleracea L.) following an identical procedure, and were used to investigate the cupric cation inhibition on the photosynthetic activity. In both species, copper inhibition showed a similar inhibitor concentration that decreases the enzyme activity by 50% (IC(50) approximately 1.8 microM) and did not depend on the internal or external phosphate (Pi) concentration, indicating that copper did not interact with the Pi translocator. Fluorescence analysis suggested that the presence of copper did not facilitate photoinhibition, because there were no changes in maximal fluorescence (F(m)) nor in basal fluorescence (F(o)) of copper-treated samples. The electron transport through the photosystem II (PSII) was also not affected (operating efficiency of PSII-F'v/F'm similar in all conditions). Yet, under Cu(2+) stress, the proportion of open PSII reaction centers was dramatically decreased, and the first quinone acceptor (Q(A)) reoxidation was fully inhibited, as demonstrated by the constant photochemical quenching (q(P)) along experiment time. The quantum yield of PSII electron transport (Phi(PSII)) was also clearly affected by copper, and therefore reduced the photochemistry efficiency. Manganese, when added simultaneously with copper, delayed the inhibition, as measured by oxygen evolution and chlorophyll fluorescence, but neither reversed the copper effect when added to copper-inhibited plastids, nor prevented the inhibition of the Hill activity of isolated copper-treated thylakoids. Our results suggest that manganese competed with copper to penetrate the chloroplast envelope. This competition seems to be specific because other divalent cations e.g. magnesium and calcium, did not interfere with the copper action in intact chloroplasts. All results do suggest that, under these conditions, the stroma proteins, such as the Calvin-Benson cycle enzymes or others are the most probable first target for the Cu(2+) action, resulting in the total inhibition of chloroplast photosynthesis and in the consequent unbalanced rate of production and consumption of the reducing power.